Practical Comparison: PowerPoint and Canva for Visual Learning - M. Ramli; Chumayroh (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2025)
This article discusses the utilization of PowerPoint and Canva as effective learning support tools in Islamic religious education. The main objective of this research is to explore the advantages, disadvantages, and optimal steps of using both platforms in designing attractive and professional presentations. With the development of digital technology, visual presentations have become an essential component in educational communication. The main results of the discussion show that PowerPoint offers great flexibility with animation features and strong data integration, while Canva excels in ease of use as well as cloud-based aesthetic design. However, each has limitations, such as the need for software installation for PowerPoint and the dependence on an internet connection for Canva.The main conclusion of this research is that these two tools can complement each other, depending on the user's needs. PowerPoint is more suitable for formal presentations that require complex animations, while Canva is ideal for creative designs with online collaboration. This research is expected to provide practical guidance for educators in choosing an appropriate tool to improve learning effectiveness.